2009
DOI: 10.29244/medkon.14.1.18-21
|View full text |Cite
|
Sign up to set email alerts
|

Kondisi Populasi Rafflesia patma Blume di Cagar Alam Pananjung Pangandaran Jawa Barat

Abstract: Rafflesia patma Blume is placed as one of the CRB2c endangered status. It refers to the taxon who face the highest extinction in the short periode of time. The flower scarce is caused by a live factor of R. patma that need specific habitats such as physical and biotic factors. The habitats and population of R. patma will be charge on fluctuation due to the higher human activities and nature's changes. The study on population of R. patma in CA Pananjung Pangandaran (CAPP) was conducted. The results indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
4
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(32 citation statements)
references
References 0 publications
4
22
4
2
Order By: Relevance
“…As for the GA plot, a total of 16 individuals recorded from the family Euphorbiaceae, resulting in the family with the highest number of individuals there. Suwartini (2008) and Rahma et al (2017) also stated that Lauraceae, Moraceae and Rubiaceae were the most dominant families found in a Rafflesia's habitat on the islands of Sumatra and Java, Indonesia. Moreover, the study of vegetation in Kinabalu Park by van der Ent et al (2016) found that Lauraceae is a predominant family around the same altitude, at 500-1000 meters above sea level.…”
Section: Floristic Compositionmentioning
confidence: 98%
See 2 more Smart Citations
“…As for the GA plot, a total of 16 individuals recorded from the family Euphorbiaceae, resulting in the family with the highest number of individuals there. Suwartini (2008) and Rahma et al (2017) also stated that Lauraceae, Moraceae and Rubiaceae were the most dominant families found in a Rafflesia's habitat on the islands of Sumatra and Java, Indonesia. Moreover, the study of vegetation in Kinabalu Park by van der Ent et al (2016) found that Lauraceae is a predominant family around the same altitude, at 500-1000 meters above sea level.…”
Section: Floristic Compositionmentioning
confidence: 98%
“…Most of the hosts found in other habitats had a larger diameter size of more than 5.0 cm. Tetrastigma leucostaphylum, the host of Rafflesia patma in West Java, has a diameter of 8.94-13.24 cm (Ali et al, 2015). Wan Norqayyum Nadia (2014) and Pranata et al (2020) also stated that the diameter size of the hosts in Lojing Highlands, Kelantan and in Panorama Baru Ngarai Sianok, West Sumatra ranged from 5.0-15.0 cm and 4.78-6.11, respectively.…”
Section: Rafflesia Population Status and Host Diametermentioning
confidence: 99%
See 1 more Smart Citation
“…Habitat yang kurang sesuai akan membuat Rafflesia patma mengalami perubahan populasi, baik secara alami maupun disebabkan oleh manusia (Mukmin, 2008). Semakin baik habitat di alam, maka populasi Rafflesia patma akan terjaga.…”
unclassified
“…Begitu juga sebaliknya, apabila habitat tidak sesuai maka populasi akan mengalami penurunan. Rafflesia patma memiliki sifat sangat rentan terhadap gangguan dan kerusakan ekologis yang disebabkan intervensi manusia di dalam kawasan (Mukmin, 2008). Cagar Alam Pangandaran merupakan kawasan yang berbatasan langsung dengan taman wisata alam, sehingga membuat pengunjung ataupun masyarakat dapat masuk ke dalam kawasan.…”
unclassified